Clinical and Systemic Consequences of Anemia in Women with Chronic Abnormal Uterine Bleeding: A Hospital-Based Study - Amber Jamil Siddiqi, Zeenat Parveen Shaikh, Shazia Ashraf, Nazneen Akhtar, Naila Javed, Lubna Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic abnormal uterine bleeding (AUB) is a frequent gynecological condition and a major cause of iron deficiency anemia among women of reproductive and perimenopausal age. Persistent menstrual blood loss leads to depletion of iron stores, resulting in anemia and a wide range of systemic consequences that adversely affect physical performance, cardiovascular function, and overall quality of life. Objective: To determine the prevalence of anemia and to evaluate its systemic consequences among women presenting with chronic abnormal uterine bleeding at tertiary care hospitals. Methods: This hospital-based cross-sectional study was conducted at the Category-D Hospital, Munda, Lower Dir, Khyber Pakhtunkhwa, and Gynecology Unit-I, Dr. Ruth K. M. Pfau Civil Hospital, Karachi, from January 2022 to February 2023. A total of 120 women aged 18–50 years with abnormal uterine bleeding persisting for more than three months were enrolled. Detailed clinical evaluation and laboratory investigations, including complete blood count, were performed. Anemia was classified according to World Health Organization criteria, and systemic manifestations were assessed and correlated with anemia severity. Results: Anemia was detected in 78.3% of women with chronic AUB. Moderate anemia was the most prevalent form (36.6%), followed by mild (31.7%) and severe anemia (10.0%). Systemic manifestations such as fatigue, generalized weakness, exertional dyspnea, palpitations, dizziness, and reduced work capacity were significantly more common in women with moderate and severe anemia. Cardiovascular signs, including tachycardia and systolic flow murmurs, increased with declining hemoglobin levels. Prolonged duration of bleeding was strongly associated with greater anemia severity. Conclusion: Anemia is highly prevalent among women with chronic abnormal uterine bleeding and is associated with significant systemic and cardiovascular consequences. Routine anemia screening and integrated management strategies addressing both abnormal uterine bleeding and iron deficiency are essential to reduce morbidity and improve patient outcomes. Keywords: Abnormal uterine bleeding; Anemia; Iron deficiency; Systemic effects; Women’s health; Cross-sectional study.